1979
DOI: 10.1590/s0006-87051979000100003
|View full text |Cite
|
Sign up to set email alerts
|

Adubação da cana-de-açúcar: XV - experimentos com micronutrientes nas regiões canavieiras do estado de São Paulo

Abstract: São apresentados os resultados de 23 experimentos em regiões canavieiras paulistas, para avaliar possíveis respostas da cana-de-açúcar a micronutrientes. Fizeram-se aplicações isoladas de sulfato ferroso, tetraborato de sódio, sulfato de cobre, sulfato de zinco, sulfato de manganês e molibdato de amônio, nos sulcos de plantio e na presença de adubação NPK Em apenas um dos experimentos verificou-se efeito significativamente favorável à aplicação de micronutrientes, no caso, cobre e molibdênio. Com base nos resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Andrade et al (1995), in an experiment with fritted trace elements-FTE (ground silicate oxides) and soluble sources of B (borax), Cu (copper sulfate) and Zn (zinc sulfate) application, verified that both joint application (FTE) as well as isolated micronutrients application did not result in increases in TSS. Older studies also did not show increases in TSS yield due to the Zn fertilization (Alvarez and Wutke 1963;Alvarez et al 1979). However, Mellis et al (2009), evaluating the micronutrients application in sugarcane in eight locations in Brazil, observed, in four sites, an average increase of 29% in TSS yield of the plant cane with the application of 3 kg ha -1 of Zn in the planting furrow.…”
Section: Yield Parameters and Technological Attributes Of Sugarcane Imentioning
confidence: 97%
See 3 more Smart Citations
“…Andrade et al (1995), in an experiment with fritted trace elements-FTE (ground silicate oxides) and soluble sources of B (borax), Cu (copper sulfate) and Zn (zinc sulfate) application, verified that both joint application (FTE) as well as isolated micronutrients application did not result in increases in TSS. Older studies also did not show increases in TSS yield due to the Zn fertilization (Alvarez and Wutke 1963;Alvarez et al 1979). However, Mellis et al (2009), evaluating the micronutrients application in sugarcane in eight locations in Brazil, observed, in four sites, an average increase of 29% in TSS yield of the plant cane with the application of 3 kg ha -1 of Zn in the planting furrow.…”
Section: Yield Parameters and Technological Attributes Of Sugarcane Imentioning
confidence: 97%
“…Espironelo et al (1976), carrying out a study involving B application in sugarcane on soil with low content of the nutrient, verified that the highest dose (8.8 kg ha -1 of B) led to toxicity in the crop and reducing the TSS yield, as well as absence of any residual effect in the first ratoon. However, most studies in the literature report the absence of yield response due to B fertilization in plant cane (Alvarez et al 1979;Azeredo and Bolsanello 1981;Mellis et al 2009). Franco et al (2009), evaluating the boric acid utilization in plant cane through the 10 B tracer, observed that fertilizer-B recovery was around 2% by the crop, indicating low fertilizer efficiency at the dose used (4 kg ha -1 of B), which may be related to losses by leaching, as emphasized in the study performed by Rosolem and Bíscaro (2007).…”
Section: Yield Parameters and Technological Attributes Of Sugarcane Imentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the absence of yield response to the other micronutrients, these were not included in the official fertilization recommendations. However, most of the studies were carried out in the 1960s, 1970s and 1980s (Spironello, 1972;IAA/Planalsucar, 1976;Alvarez et al, 1979;Azeredo & Bolsanello, 1981) with older cultivars with lower production potential.…”
Section: Introductionmentioning
confidence: 99%